Streptococcus Pneumoniae septic arthritis in adults in Bristol and Bath, United Kingdom, 2006–2018: a 13-year retrospective observational cohort study. Issue 1 (1st January 2021) - Hyams, Catherine; Amin-Chowdhury, Zahin; Fry, Norman K.; North, Paul; Finn, Adam; Judge, Andrew; Ladhani, Shamez N.; Williams, O. Martin
ABSTRACT: Few studies on adult pneumococcal septic arthritis are sufficiently large enough to assess both epidemiological trends following routine pneumococcal immunization and clinical disease. With major shifts in serotypes causing invasive pneumococcal disease (IPD), we wanted to determine the clinical phenotype of adult septic arthritis caused by Streptococcus pneumoniae . We conducted a retrospective cohort study of pneumococcal infections in Bristol and Bath, UK, 2006–2018. We defined pneumococcal septic arthritis as adults with clinically-confirmed septic arthritis, with pneumococcus isolated from sterile-site culture or urinary antigen test positivity. Clinical records were reviewed for each patient in the cohort. Septic arthritis accounted for 1.7% of all IPD cases. 45 cases of adult pneumococcal septic arthritis occurred, with disease typically affecting older adults and those with underlying comorbidity. 67% patients had another focus of infection during their illness. 66% patients required increased care on discharge and 43% had reduced range of movement. In-hospital case fatality rate was 6.7%. One-year patient mortality was 31%. Currently most cases of adult pneumococcal septic arthritis are due to non-PCV13 serotypes which are associated with more severe disease. Non-PCV-13 serotypes had higher prevalence of concomitant pneumococcal infection at another site (73.7% versus 36.6%), increased intensive care or high-dependency unit requirement (32.4% versus 0%), and increased inpatient and 1-year case fatality rate (8.8% versus 0%, and 32.4% versus 27.4% respectively) compared to PCV-13 serotypes. Pneumococcal septic arthritis remains a small proportion of IPD. However, there is significant associated morbidity and mortality, and pneumococcal septic arthritis requires monitoring in coming years.